A Review of the Research on Electro-hydraulic Load Simulator and Characteristics with Improvement Methods - LI, Jianying; Li, Weidong; Liang, Heng; Kong, Lingbing (Recent Patents on Engineering, 2024)
The electro-hydraulic load simulator is a semi-physical simulation system. It is used to simulate different loads on the bearing capacity object (steering gear system) under working conditions and further test the dynamic and static characteristics of the bearing capacity object. Therefore, it is widely used in important applications such as the simulation of various loads and the development of high-performance steering gear systems. By analyzing and discussing the electro-hydraulic load simulator equipment and its improvement methods, some useful conclusions have been drawn to predict the development of the electro-hydraulic load simulator and its key technologies. The current status of research on electro-hydraulic load simulator prototypes is discussed in depth. The electro-hydraulic load simulators are classified according to the loading system applying force (torque). The improvement methods of the electro-hydraulic load simulator, including the method of suppressing the extraneous force, the compensation method of nonlinear factors, and the method of establishing the mathematical model, are analyzed and summarized. By summarizing the literature and patents on electro-hydraulic load simulation technology, the principle, and characteristics of different equipment and improvement methods are analyzed and compared, and future development of electro-hydraulic load simulation equipment and technology is discussed. The research on the characteristics of the prototype, the hardware means and control strategy to suppress the extraneous force, the compensation of nonlinear factors, and the methods of establishing the mathematical model are beneficial to improve the loading accuracy of the electro-hydraulic load simulator.
Keywords: loading system